Pengaruh Good Corporate Governance Dan Corporate Social Responsibility Terhadap Kinerja Keuangan Pada Perusahaan Keuangan Di Bursa Efek Indonesia : GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY - Rodhiyani Cahya Ningsih; Dian Retnaningdiah (Jurnal Solusi, 2021)
this study was to determine the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on Financial Performance as measured by Return on Assets (ROA) in financial companies listed on the IDX in the period of 2014-2018. This study used a Multiple Linear Regression Analysis. The independent variable of the research used GCG as proxied by the Board of Directors, Proportion of Independent Commissioners, Managerial Ownership, Institutional Ownership, and the Audit Committee, while CSR is measured using indicators based on the 2016 Global Reporting Inititive (GRI) Standard. Financial performance as measured by Return on Assets (ROA). Sampling data using purposive sampling, and there are 11 companies that meet predetermined criteria. This study showed that the Managerial Ownership has an effect on Financial Performance (ROA). This is shown as hypothesized. The Board of Directors, the Proportion of Independent Commissioners, Institutional Ownership, the Audit Committee do not affect the Financial Performance (ROA), this is not as hypothesized. CSR has no effect on Financial Performance (ROA), this is not what was hypothesized. The Board of Directors, Proportion of Independent Commissioners, Managerial Ownership, Institutional Ownership, Audit Committee and CSR simultaneously affect Financial Performance (ROA). These results meet the hypotheses of the study. Keywords: Good Corporate Governance, Corporate Social Responsibility, Financial Performance